Architectural technology - Emmitt, Stephen (Hoboken : Wiley-Blackwell, 2012)
Since the publication of the first edition of Architectural Technology, in 2002, there have been significant developments in the number of courses, the profile of the discipline as well as significant changes in the Construction sector. The Second edition of Architectural Technology addresses these challenges directly.
Includes bibliographical references (p. [229]-234) and index.
Keywords: Architecture -- Technological innovations; Architecture and technology; Architectural design -- Technique